Low‐Temperature Direct Catalytic Hydrothermal Conversion of Biomass Cellulose to Light Hydrocarbons over Pt/Zeolite Catalysts. Issue 22 (12th July 2017) - Ogo, Shuhei; Okuno, Yutaro; Sekine, Hikaru; Manabe, Shota; Yabe, Tomohiro; Onda, Ayumu; Sekine, Yasushi
Abstract: Direct catalytic hydrothermal conversion of cellulose to C3 +C4 hydrocarbons at a low temperature (443 K) over a Pt/zeolite catalyst without hydrogen or other expensive reagents was investigated. Pt supported on NH4 + ‐form ultra‐stable Y‐type (NH4 ‐USY) zeolite catalyst, which showed the highest activity among the tested Pt/zeolite catalysts, has appropriate acidity and a suitable active Pt site. The C3 +C4 hydrocarbon yield reached 14.5 C‐% during the reaction over the Pt/NH4 ‐USY catalyst at 443 K after 72 h of the reaction. Results showed that the acid strength of the zeolite support was an important factor affecting the cellulose decomposition activity. Because of their structural sensitivity, Pt/zeolite catalysts with Pt particles larger than 5 nm, including Pt/NH4 ‐USY catalyst, showed higher TOF values than catalysts with Pt particles smaller than 5 nm. Abstract : Cellulose was directly converted to C3 +C4 hydrocarbons by a bifunctional catalysis of Pt supported on zeolite catalyst, even at 443 K, under hydrothermal condition. Because of their structural sensitivity, Pt/zeolite catalysts with Pt particles larger than 5 nm showed higher TOF values.